What features of a nutrition resource are important to adolescents of a low socioeconomic status?. Issue 10 (27th July 2020) - Scott, HC; Craddock, C; Craig, LCA
Abstract: Objective: To identify the key features of a nutrition resource that are important to adolescents of a low socioeconomic status (SES). Design: Structured interviews were conducted to explore participants' preferences relating to the features of a nutrition resource. Thematic framework analysis was used to determine key themes, subthemes and concepts from the data. Setting: Streetsport activity sessions, north-east of Scotland. Participants: Eighteen adolescents aged 12–17 years from a low socioeconomic background. Results: The overarching themes identified were barriers and facilitators to engagement with a nutrition resource. Adolescents expressed a preference for an app, and this was mainly attributed to convenience and low cost. There was also an emphasis on the integral role social media has in their lives. Aesthetics was a facilitator for both male and female participants, with a particular focus on weight loss. Behaviour change support, including reminders, access to simple recipes and adopting a 'small change approach', were identified as possible facilitators, whereas cost, environmental influences, and existing eating habits were identified as possible barriers to engaging with a nutrition resource. Conclusions: A number of subthemes, including aesthetics, cost and convenience, which have previously been reported in adolescents with a higher SES, were prominent in our research. The present study contributes to insights relating to behaviour change tools that should be considered when developing a nutrition resource targeting disadvantaged adolescents. Further research focusing on how mobile phone technology and social media can be utilised to support dietary behaviour change in low SES adolescents is recommended.